2013
DOI: 10.1071/ah11077
|View full text |Cite
|
Sign up to set email alerts
|

The ebbs and flows of changing acute bed capacity delays

Abstract: The Capacity Audit process and tool has been used to track progress, trends and change resulting from service improvement efforts, and to provide the evidence to commence strategies to reduce the hidden capacity issues. This case study has shown that whilst overall bed stock usage for positive care has not changed significantly there are various ebbs and flows over time in relation to the reasons for bed delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…15,19 ALC creates a ripple effect through the entire care pathway-starting in the emergency room, where patients may be stuck waiting for hours on stretchers in hallways (also referred to as 'hallway medicine') 20 to cancelled surgeries and compromised access to post-surgical rehabilitation and other treatments. 6,20 That said, ALC is a symptom of a poorly functioning healthcare system, 20 characterized by hospital process issues (delays in assessment or lack of consensus on next steps in care), [21][22][23] postacute care capacity issues (lack of timely and suitable housing, rehabilitation and home care services) 5,[23][24][25][26][27][28][29] or lack of long-term care beds (particularly beds that are tailored to the linguistic, cultural and geographical preferences of patients and caregivers). [30][31][32][33] Simply put, the ALC problem represents a mismatch between available care services and the needs of patients and their caregivers.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…15,19 ALC creates a ripple effect through the entire care pathway-starting in the emergency room, where patients may be stuck waiting for hours on stretchers in hallways (also referred to as 'hallway medicine') 20 to cancelled surgeries and compromised access to post-surgical rehabilitation and other treatments. 6,20 That said, ALC is a symptom of a poorly functioning healthcare system, 20 characterized by hospital process issues (delays in assessment or lack of consensus on next steps in care), [21][22][23] postacute care capacity issues (lack of timely and suitable housing, rehabilitation and home care services) 5,[23][24][25][26][27][28][29] or lack of long-term care beds (particularly beds that are tailored to the linguistic, cultural and geographical preferences of patients and caregivers). [30][31][32][33] Simply put, the ALC problem represents a mismatch between available care services and the needs of patients and their caregivers.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Achieving these targets helps hospitals reduce access block (also known as boarding), improve flow in their EDs and keep occupancy below critical levels . Poor discharge planning, poor communication and other non‐medical reasons have been credited with being responsible for delayed discharges . However, several intervention projects have demonstrated the ability to achieve more timely discharge .…”
Section: Introductionmentioning
confidence: 99%
“…7 Poor discharge planning, poor communication and other nonmedical reasons have been credited with being responsible for delayed discharges. [8][9][10][11] However, several intervention projects have demonstrated the ability to achieve more timely discharge. 2,[12][13][14] A contrary view is that aiming for morning…”
Section: Introductionmentioning
confidence: 99%
“…Improving hospital patient flow is important in order to optimise the use of limited healthcare resources efficiently, 1 minimise iatrogenic adverse events, 2 and it may ensure patient-centred care. 3,4 Numerous studies have identified problems with patient flow in the emergency department, [5][6][7] acute care 8,9 and rehabilitation hospitals. 10,11 Barriers to discharge from hospital are common, with reports that these occur in approximately 14-16% of acute hospital 12,13 and rehabilitation admissions.…”
Section: Introductionmentioning
confidence: 99%